Saberes locais e processo de ensino-aprendizagem nas séries iniciais da EMEF Petronília do Carmo/Comunidade Quilombola Itamoari - Cachoeira do Piriá/PA - TEMBE, Lucirlandia Oliveira Santos (2024)
The article deals with local knowledge and the teaching-learning process in the initial grades of elementary school in a quilombola community, municipality of Cachoeira do Piriá, the northeastern region of the state of Pará. The general goal is to analyze how traditional knowledge influences the teaching and learning of students in the initial grades of elementary school, specifically in the literacy process. The study is based on a qualitative approach of bibliographic nature and field research. The field research was carried out in a public school, with the following subjects: two teachers, eight quilombola students, and a community representative. The references for this work are based on authors who discuss Quilombola Education, the National Guidelines and Bases for Quilombola Education. The knowledges of the quilombola community must be considered in educational activities; they must permeate the exercise of pedagogical practices, being evidenced in the reading of the protagonists’ world words of the protagonists and belongings, enabling effective literacy, commencing from their realities and preceding the reading of the written word, aiming at the human emancipation of its subjects. The results indicated that it is possible to build, under other perspectives, literacy practices immersed in the cultural production of traditional knowledge that emerges from the existential diversity and singularities of lives in the quilombo of the Amazon in Pará.